Meat Market - A Regional Study of Consumer Preferences And Behaviour - Cristian DELIBAS; Mioara MIHAILA; Andy-Felix JITAREANU; Bianca-Antonela UNGUREANU; Stefan VIZITEU; Elena LEONTE; Mioara MIHAILA (Communications of International Proceedings, 2022)
The study of consumer behaviour is one of the most challenging concerns of marketing, having a high relevance both in research and for production or marketing decisions and strategies. This paper is a regional study on the behaviour and consumption preferences for the food "meat and meat products". The quantitative research, of empirical order, is based on the market investigation and follows the dynamics of the attributes that contribute to the manifestation of the consumption behaviour for the analysed product and to the expression of the purchase decision. The survey was conducted on a sample of 450 subjects from the North-East Development Region of Romania, and led to a set of results relevant to the formation of a current and perspective image of the national meat market. The main results obtained are: consumers choose products based on quality and impact on health, price is not relevant for purchase and consumption, brand loyalty is very significant, meat consumption in Romania has an upward dynamic and takes into account both the traditions of consumption, as well as the interest in health. The chosen theme is justified by the high production potential on the national market of this specific product, an aspect that can be capitalized in favour of supporting domestic producers and ensuring national food security.
Keywords: meat market; consumer preferences; consumption behaviour; customer satisfaction